Indonesian Government In The Development Of The Global Electric Vehicle Industry Through Investment And Nickel Downstream - Annisa Millania Wildhani; Dyah Mutiarin (Jurnal Ekonomi dan Studi Pembangunan, 2024)
This study aims to analyze the role of the Indonesian government in developing the global electric vehicle industry through the potential of nickel. This research focuses on investment and downstream case studies in Indonesia. The aim is to evaluate the strategic steps taken by the government in attracting investors and encouraging downstream activities for Indonesia's nickel potential in supporting economic growth. This research was conducted using qualitative research methods by presenting findings through online media, this research data comes from online news media. This data was obtained using the Ncapture feature on Nvivo 12 Plus. The results of the study show that the role and strategic steps taken by the Indonesian government in nickel downstream and investment in Indonesia are largest in downstream by 40.74%, secondly in export bans by 24.07%, thirdly in nickel smelter investment by 18.52% and finally, the development of the battery and electric vehicle industry at 16.67 and the results of wordcloud analysis show that the most popular words on the issue of nickel potential development are downstream export bans, electric smelters, and also electric vehicles